Between the Written Sources and the Liturgical Calendar: An Approach to the Study of Pregnant Annunciations - Ibáñez Palomo, Tomás (Eikón / Imago, 2016)
Between the 13th and 15th centuries a new way of portraying the Annunciation was developed in the Iberian Peninsula. This iconographic variant, which depicts the Virgin in an advanced state of pregnancy, enjoyed great acceptance in the territories of the Crown of Castile and the Kingdom of Portugal. Even though there is no unanimous agreement on the reasons for this emphasis on the pregnancy, most researchers coincide in pointing out the transfer of the feast in the Hispanic Rite —from the 25th of March to the 18th of December, giving rise to the so called Feast of the Expectation— as the main potential cause. This article is intended to make an approach to the sources of the passage, seeking for possible connections with the features that typify these Annunciations, without losing sight of the influential capacity that the new feast of December had, as did the writings of Saint Ildephonsus of Toledo, its alleged creator.